2022
DOI: 10.1177/09612033221148099
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation alterations in systemic lupus erythematosus: A systematic review of case-control studies

Abstract: Background Traditionally, the diagnosis and monitoring of disease activity in systemic lupus erythematosus (SLE) are contingent upon clinical manifestations and serological markers. However, researchers are struggling to find biomarkers with higher sensitivity and specificity. DNA methylation has been the most studied epigenetic feature in SLE. So, in this study, we performed a systematic review of studies about DNA methylation alterations in SLE patients compared to healthy controls. Methods By searching PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…This is consistent with the findings of three previous studies on methylation analysis in SLE patients, specifically a potential biomarker called IFI44 L. 19,23,31 Also, in a recent study, our research team unveiled that the methylation level of the MMP9 gene can appreciably discriminate SLE patients from healthy control population. 18 Furthermore, we observed that SLE patients with renal involvement exhibited higher methylation levels in the RUNX3 promoter sequence compared to those without renal involvement. Additionally, there was a positive correlation between the methylation level of RUNX3 and creatinine concentration, suggesting that abnormal methylation leading to functional disruption of this gene could potentially contribute to lupus nephritis.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This is consistent with the findings of three previous studies on methylation analysis in SLE patients, specifically a potential biomarker called IFI44 L. 19,23,31 Also, in a recent study, our research team unveiled that the methylation level of the MMP9 gene can appreciably discriminate SLE patients from healthy control population. 18 Furthermore, we observed that SLE patients with renal involvement exhibited higher methylation levels in the RUNX3 promoter sequence compared to those without renal involvement. Additionally, there was a positive correlation between the methylation level of RUNX3 and creatinine concentration, suggesting that abnormal methylation leading to functional disruption of this gene could potentially contribute to lupus nephritis.…”
Section: Discussionmentioning
confidence: 68%
“…The sample size was calculated regarding the previously reported frequency of GATA3 methylation in the normal general population [15][16][17] and methylation studies in the Iranian SLE patients. [18][19][20][21][22][23] The samples were taken from a vein and stored in tubes containing an anticoagulant called EDTA. The stored samples were kept at a temperature of À20°C for further processing.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Furthermore, differential DNA methylation between SLE patients and healthy people with a variety of hypo- or hypermethylation patterns has been investigated at the level of single genes which are involved in the function of the immune system such as IFI44L , MX1 , FOXP3 , and so on. 12…”
Section: Introductionmentioning
confidence: 99%
“…11 Furthermore, differential DNA methylation between SLE patients and healthy people with a variety of hypo-or hypermethylation patterns has been investigated at the level of single genes which are involved in the function of the immune system such as IFI44L, MX1, FOXP3, and so on. 12 Currently, the diagnosis of SLE and measurement of disease activity in patients are mainly contingent upon clinical phenotypes and serological markers comprising anti-Smith (anti-Sm) antibodies, anti-double-stranded DNA (anti-dsDNA) antibodies, anti-nuclear antibodies (ANAs), erythrocyte sedimentation rate (ESR), rheumatoid factor (RF), complement proteins (C3 and C4), and C-reactive protein (CRP). 13,14 Current guidelines for SLE diagnosis propose that the mentioned serological markers should be interpreted together; notwithstanding, some studies have demonstrated the low sensitivity and specificity of these factors.…”
Section: Introductionmentioning
confidence: 99%